Estudo da infiltração de tecidos orais em pacientes com doenças hematológicas malignas - Ana Carolina Velasco Pondé de Sena (2022)
This work carried out a retrospective study of the medical records at the Hospital das Clínicas (HC), Universidade Federal de Minas Gerais (UFMG). Individuals admitted in the period from 2010 to 2021 with a diagnosis of leukaemia/lymphoma and who were evaluated by the team of the dental service of HC-UFMG were included. Demographic data, clinical characteristics of the underlying disease and oral cavity, and presence of malignant oral infiltration were collected. The unpaired t test was employed to assess the blood count and the McNemar test to compare individuals who developed malignant oral infiltration and those who did not. Statistical significance was set at p<0.05. Additionally, a literature review of case reports and case series was undertaken in four electronic databases (PubMed, Web of Science, Scopus, and Embase). Of the 781 medical records analysed, acute lymphocytic leukaemia (30.1%) was the most frequent diagnosis. Patients in the first two decades of life were more affected by the underlying disease. Caries (36.7%) and periodontal changes (34.6%) were the most frequently observed oral conditions. Oral malignant infiltration took place in 25 (3.2%) individuals, mainly involving the gingiva (80%) and individuals diagnosed with acute myeloid leukaemia (64%). Comparing data from paediatric patients who developed malignant infiltration and those who did not, the proportion of deaths was higher in those who had infiltration (p=0.002), while in adults, those who developed infiltration had worse periodontal status and a higher proportion of death (p<0.001). Data from the literature review showed that oral malignant infiltration was more frequent in the gingiva (37%) and in patients with acute myeloid leukaemia (47%). The main clinical and imaging features associated with oral infiltration were swelling and osteolytic lesions. Altogether, the data suggest the importance of clinical dental monitoring of patients with leukaemia/lymphoma considering the worst clinical outcomes related to oral tissue infiltration.